Foliar salicylic acid application to mitigate the effect of water deficiency on potato (Solanum tuberosum L.) - Acevedo, Andres Felipe Gaona [UNESP]; Lacerda, Vander Rocha [UNESP]; Gomes, Jonath Werissimo da Silva; Avilez, Alberto Mario Arroyo [UNESP]; Fernando, Broetto; Sarria, Saul Dussan; Vieites, Rogerio Lopes [UNESP] (Elsevier, 2023)
Water deficiency (WD) is one of the main factors that limit the growth and productivity of crops in the world. Salicylic acid (SA) is considered a plant hormone that has an important role in the plants’ growth, development, and tolerance to abiotic stress. There is a hypothesis that the application of SA could mitigate the impact of the physical stress in potato plants. From the imposition of WD the physiological and biochemical indexes, including the antioxidative defense system, were evaluated in potato plants treated with the foliar application of SA. The assay revealed that the moderate WD 45 kPa negatively affected the metabolic parameters in potato plants. Foliar application of SA presented positive effects in the mitigation of oxidative damage through the dismutation of reactive oxygen species (ROS), suggesting the protection of the cellular membrane structure. Furthermore, there was less accumulation of malondialdehyde and synthesis of bioactive compounds, which certainly increased the antioxidative capacity of the plants. In conclusion, the results indicate that the foliar application of SA can have a positive regulatory role in alleviate water deficiency stress in potato plants.
Keywords: Salicylic acid; Potato; Abiotic stress; Bioactive compounds